Band gap tuning of BaFe12O19 with Mg and Mn doping to enhance solar light absorption for photocatalytic application. (6th March 2021) - Bibi, Ismat; Naz, Tahmina; Majid, Farzana; Kamal, Shagufta; Ata, Sadia; Almoneef, Maha M.; Iqbal, Shahid; Iqbal, Munawar
Summary: Mg and Mn ions doping were performed in barium hexaferrite (Ba1−x Mgx Fe12−y Mny O19 ) (x = 0.0, 0.30, 0.45, 0.60, 0.75, 0.90) and (y = 0.0, 0.15, 0.30, 0.45, 0.60, 0.75) via facile micro‐emulsion route. XRD analysis revealed the formation of single‐phase hexagonal geometry of Ba1−x Mgx Fe12−y Mny O19 with the successful doping of the Mg and Mn ions. The average crystallite size was 19.5 nm, which was increased by increasing the dopant contents. The functional groups were identified by FTIR analysis. The dopant contents (Mg and Mn) affected the dielectric properties Ba1−x Mgx Fe12−y Mny O19 and AC conductivity was increased, while dielectric loss, tangent loss, and resistivity were decreased as the concentration of dopant ions was increased. The Tauc's plot was used for the band gap estimation of Ba1−x Mgx Fe12−y Mny O19, the band gap values were decreased from 2.94 to 1.90 (eV) due to generation Fermi energy and change in the Ba 2+ ions at the tetra‐ and octahedral locations. Photocatalytic activity (PCA) was performed under visible light by degrading Rhodamine B (RhB) dye. The RhB dye was degraded up to 85% within 50 minutes following the first order reaction kinetics with 0.0224 min −1 rate constant. The results revealed that the BaFe12 O19 NPs the band gap can be tuned by doping the Mg and Mn ions to enhance the visible light harvesting for economical photocatalytic applications in various fields. Abstract : Mg and Mn ions doped barium hexaferrite (Ba1‐xMgxFe12‐yMnyO19) was prepared via micro‐emulsion route. The doping of Mg and Mn ions significantly affected the structural, dielectric, optical and photocatalytic properties of the barium ferrite. Hence, Ba1‐xMgxFe12‐yMnyO19 could have potential photocatalytic applications under solar light irradiation.